Odpowiedzi

2010-01-29T19:42:43+01:00
A) 4a- ( -2a+3)= 4a + 2a - 3 = 6a - 3
b) -7x - ( 3y-4x-2)= - 7x - 3y + 4x + 2 = -3x -3 y + 2
c) (4x - 7) -( 10x+2)= 4x - 7 - 10x - 2 = - 6x - 9
d) ( 2a+3) - ( a-5)-(-2a+1)= 2a + 3 - a + 5 + 2a - 1 = 3a + 7
  • Użytkownik Zadane
2010-01-29T19:44:58+01:00
A) 4a - ( -2a +3 ) =4a+2a-3=6a-3
b) -7x - ( 3y - 4x - 2 ) =-7x-3y+4x+2=-3x-3y+2
c) ( 4x - 7 ) - ( 10x + 2 ) =4x-7-10x-2=-6x-9
d) ( 2a +3 ) - ( a - 5 ) - ( -2a +1 ) =2a+3-a+5+2a-1=3a+7
2010-01-29T19:45:23+01:00
A)4a+2a-3=6a-3
b)-7x-3y+4x+2=-3x-3y+2
c)4x-7-10x-2=-6x-9
d)2a+3-a+5+2a-1=3a+7